The Effect of Work Capacity and Training in Improving Employee Performance at PT Indofood Cbp Sukses Makmur Tbk - Abimanyu Mahardikaputra; Asim (JKEN: Jurnal Kajian Ekonomi Nasional, 2025)
This study aims to analyze the influence of work ability and training on employee performance at PT Indofood CBP Sukses Makmur Tbk. This study was conducted in Jakarta using quantitative methods. The sampling technique used was saturation sampling, involving 100 respondents. Primary data was collected through questionnaires and analyzed using SPSS software version 22.0. The analysis results indicate that work ability and training partially have a positive and significant effect on employee performance. Furthermore, work ability also had a positive and significant effect on training. Keywords: Work Ability; Training; Employee Performance.